2023
DOI: 10.7759/cureus.48237
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor (BDNF) Concentration Levels in Cerebrospinal Fluid and Plasma in Patients With Glioblastoma: A Prospective, Observational, Controlled Study

Katarzyna Wójtowicz,
Katarzyna Czarzasta,
Lukasz Przepiorka
et al.

Abstract: Objective Glioblastomas (GBMs) are among the most frequent and most malignant of untreatable brain tumors. A GBM marker could accelerate diagnosis and facilitate therapeutic monitoring. This prospective, observational, controlled study compared brain-derived neurotrophic factor (BDNF) levels in cerebrospinal fluid (CSF) and plasma between patients with GBM and a control group. Materials and methods Patients in the observational group underwent elective GBM resection (n=24, 55.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Increased expression of BDNF has been observed in multiple cancers such as breast cancer ( 22 ), glioblastoma ( 23 ), and neuroblastoma ( 7 ), and its expression is associated with poor prognosis ( 11 , 24 ). Similar to NGF, BDNF can activate pathways that increase cell survival and proliferation through TrkB receptor by activating a series of downstream pathways including phosphoinositide-3-kinase (PI3K)/Akt, mitogen-activated protein kinase (MAPK), phospholipase C-γ (PLCγ), and epidermal growth factor receptor (EGFR).…”
Section: Interactions Between Cancer Cells and Peripheral Nervementioning
confidence: 99%
“…Increased expression of BDNF has been observed in multiple cancers such as breast cancer ( 22 ), glioblastoma ( 23 ), and neuroblastoma ( 7 ), and its expression is associated with poor prognosis ( 11 , 24 ). Similar to NGF, BDNF can activate pathways that increase cell survival and proliferation through TrkB receptor by activating a series of downstream pathways including phosphoinositide-3-kinase (PI3K)/Akt, mitogen-activated protein kinase (MAPK), phospholipase C-γ (PLCγ), and epidermal growth factor receptor (EGFR).…”
Section: Interactions Between Cancer Cells and Peripheral Nervementioning
confidence: 99%
“…It was previously demonstrated that 1-week wheel-running intervention increased the global acetylation of histone 3 in the hippocampus of mice, thereby, increasing the transcription of BDNF (60). Recent studies have demonstrated that patients with GBM exhibited reduced levels of BDNF in both their plasma and cerebrospinal fluid, potentially being associated with cognitive decline in GBM (61,62). Although several studies have shown that the adjuvant therapeutic role of exercise functions through epigenetic modification in patients with cancer (54), no studies to date have examined the therapeutic effect of exercise on epigenetic modification in patients with GBM, at least to the best of our knowledge.…”
Section: Physiological and Therapeutic Mechanisms Of Exercise In Cancermentioning
confidence: 99%